Comparative study of presidential elections 2017 and 2022 in Timor-Leste - Martins, Francisco Siquera; Rui da Cruz; Leonito M. Martins (PT FORMOSA CENDEKIA GLOBAL, 2024)
A comparative study is an activity that aims to increase the knowledge and knowledge that will be applied in the future to improve. This type of activity is particularly good for the performance of the organisation, the 2017 President's election has shown something different from the perception and doubts that have previously emerged in the public about peace and stability, In the 2022 President's election, the Timorese has determined who is the President of the country for the next five years. The problem identified by this research is that the 2017 President of the Republic's elections have shown a different from the precepts and doubts that have previously emerged in the public about the peace and stability of the 2017 President's elections (CNE) and (STAE) - which have a general supervision mandate and implement this competence respectively, transmit confidence in their management capacity and offer a good and inclusive elections. Many of the voters came to vote and were able to exercise their right to vote in secret, free from any interference and in a calm environment